"Engines and Wagons”: The Challenges and Options of Conserving Railway Heritage - Simbarashe Shadreck Chitima (SAGE Publications, 2022)
Zimbabwe has a rich railway heritage that includes rail engines, wagons, coaches, trolleys, ticket rooms, rail stations, and tracks. The National Railway Museum of Zimbabwe (NRMZ) has a long history in providing railway transport and have contributed to the social, economic, and political lives of Zimbabweans. The NRMZ is the only institution that collects, preserve, and display railway heritage. This study investigates the effectiveness of the NRMZ in conserving railway heritage. This study employed qualitative research methodology. It is revealed that railway collections are deteriorating at unprecedented levels. The major agents of deterioration include relative humidity, temperature, pollution, pests and rodents as well as human factors. The study concludes that the NRMZ is employing ineffective conservation strategies and the museum is likely to lose more collections if they do not prioritize preventive conservation, develop collections, and disaster management policies.